2020
DOI: 10.1080/17453674.2020.1754645
|View full text |Cite
|
Sign up to set email alerts
|

No association between waiting time to surgery and mortality for healthier patients with hip fracture: a nationwide Swedish cohort of 59,675 patients

Abstract: Background and purpose — Waiting time to surgery for patients with hip fractures and its potential association with mortality has been frequently studied with the hypothesis that longer waiting time is associated with adverse outcomes. However, despite numerous studies, there is no consensus regarding which time frames are appropriate, and whether some patients are more vulnerable to waiting than others. We explored the association between waiting time to surgery and short-term mortality and whether sex, age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 16 publications
4
23
0
Order By: Relevance
“… 2009 , Greve et al. 2020 ). Other studies have shown a similar low mortality rate after a hip fracture in young patients (Robinson et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2009 , Greve et al. 2020 ). Other studies have shown a similar low mortality rate after a hip fracture in young patients (Robinson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous patients suffer from disability after a hip fracture and the 4-month mortality rate has recently been reported to be as high as 16% in patients older than 65 years of age (Greve et al. 2020 ). However, patients with hip fractures do not form a uniform entity.…”
mentioning
confidence: 99%
“…Elderly patients with hip fractures have higher mortality risk following surgical delay, a risk that is enhanced in men and patients with multiple comorbidities (Beaupre et al 2019). Greve et al (2020) reported higher mortality in patients with an ASA score of 3-4, but surprisingly also in women, when surgical waiting time was > 24 hours from admission. All this has led to an effort in many countries to operate hip fractures within 24 hours-or as the NICE guidelines in the UK say, "perform surgery on the day of, or the day after, admission" (National Institute for Health and Care Excellence 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(5) Since then, several high-quality registry studies have been published. (11)(12)(13)(14) An updated analysis of existing data is therefore required to review and inform guidelines for the management of hip fractures.…”
Section: Introductionmentioning
confidence: 99%